Functional Echomyography of the human denervated muscle: first results - Riccardo Zanato; Leonora Martino; Roberto Stramare (PAGEPress Publications, 2011)
In this study we followed with ultrasound three patients with permanent denervation to evaluate changes in morphology, thickness, contraction and vascularisation of muscles undergoing the home-based electrical stimulation program of the Rise2-Italy project. During a period of 1 year for the first subject, 6 months for the second subject and 3 months for the third subject we studied with ultrasound the denervated muscle comparing it (if possible) to the contralateral normal muscle. We evaluated: 1. Changes in morphology and sonographic structure of the pathologic muscle; 2. Muscular thickness in response to the electrical stimulation therapy; 3. Short-term modifications in muscle perfusion and arterial flow patterns after stimulation; 4. Contraction-relaxation kinetic induced by volitional activity or electrical stimulation. Morphology and ultrasonographic structure of the denervated muscles changed during the period of stimulation from a pattern typical of complete muscular atrophy to a pattern which might be considered “normal” when detected in an old patient. Thickness improved significantly more in the middle third than in the proximal and distal third of the denervated muscle, reaching in the last measurements of the first subject approximately the same thickness as the contralateral normal muscle. In all the measurements done within this study, arterial flow of the denervated muscle showed at rest a low-resistance pattern with Doppler Ultra Sound (US), and a pulsed pattern after electrical stimulation. The stimulation- induced pattern is similar to the trifasic high-resistance pattern of the normal muscle. Contraction- relaxation kinetic, measured by recording the muscular movements during electrical stimulation, showed an abnormal behaviour of the denervated muscle during the relaxation phase, which resulted to be significantly longer than in normal muscle (880 msec in the denervated muscle vs 240 msec in the contralateral normal one). The very high energy needed to stimulate the denervated muscles according to the Vienna home-based Functional Electrical Stimulation (h-b FES) strategy demonstrates that the explored muscles are denervated. This pilot study confirms the usefulness of Functional EchoMyography in the follow-up and the positive effects of h-b FES of denervated/reinnervating muscles.